Temporal changes in soil carbon and nitrogen in response to grazing management and vegetation cover in south-eastern Australia - David B. Lindenmayer; Daniel Florance; Benjamin Scheele; Elle Bowd; Craig Strong; Andrew Macintosh; Maldwyn John Evans (PLoS ONE, 2026)
Maintaining appropriate levels of carbon and nitrogen in soils is critical to the maintenance of productivity in agricultural systems. However, results vary from studies on the influence of land management, such as livestock grazing, on soil carbon and soil nitrogen. A large-scale study was implemented to quantify relationships between soil carbon, nitrogen, carbon:nitrogen ratio (C:N ratio), grazing regimes, and vegetation cover at sites on farms in south-eastern Australia, sampled in 2011 and 2022. Three grazing regimes were examined: total livestock exclusion, rotational grazing (limited duration grazing up to 45 days annually), and (continuous) set stocking rate grazing. Statistically modelled mean values for soil carbon (2011: 3%, 2022: 3.73%), nitrogen (2011: 0.21%, 2022: 0.34%), and C:N ratio (2011: 13.9, 2022: 14.3) were greater in 2022 than 2011. Soil carbon and nitrogen were greater in 2022 than 2011 in continuous grazing sites, with less pronounced time period differences in grazing exclusion and rotational sites. The C:N ratio was significantly greater in 2022 than 2011 in grazing exclusion sites (2011: 13.73, 2022: 14.58) and rotational grazing sites (2011: 13.87, 2022: 14.49), but less in 2022 (13.59) relative to 2011 in continuous grazing sites (14.31). There were inconsistent (sometimes positive, sometimes negative) empirical relationships between grazing regimes and vegetation measures as well as relationships between vegetation measures and soil carbon, soil nitrogen, and C:N ratio. Structural equation modelling (SEM) revealed limited evidence for soil carbon changes in response to vegetation attributes impacted by grazing regimes. Lower values of soil nitrogen and higher values for the C:N ratio at grazing exclusion sites were mediated by an increase in sapling abundance. SEM also identified an influence of rainfall on vegetation attributes, some of which were associated with soil properties.